State of the art for walking as a transport mode within 15-minute cities - Luisa Merlo; Charlotta Johansson; Finn Nilson; David Chapman (Urban, Planning and Transport Research)
Walking is well known for its societal benefits, including promoting sustainability, health, and environmental well-being. In recent years, urban planners and traffic designers have increased their focus on creating pedestrian-friendly zones. The 15-minute city concept, which gained recognition in recent years, emphasizes proximity, aiming to keep daily amenities close to residents to reduce travel time and encourage walking and cycling as modes of transport. This literature review, using an abductive qualitative approach, examines how the factors influencing planning for walking are addressed within the 15-minute city concept. The goal is to compile the state of knowledge and identify critical issues and priorities in the field of walking as a mode of transport. The findings are predominantly from China and Italy, and indicate a global concern about urban centres’ accessibility within the 15-minute city concept and highlight that walking is a multidisciplinary topic. However, the review reveals under-researched areas such as individual factors, smaller settlements, and lack of standardized methods. This stresses the need for further research to encourage walking and its multiple benefits.